2014
DOI: 10.1002/app.41656
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites of poly(3‐hydroxybutyrate)/organomodified montmorillonite: Effect of the nanofiller on the polymer's biodegradation

Abstract: Poly(3-hydroxybutyrate) (PHB) is a biopolymer that can be degraded by extracellular PHB depolymerase. This enzyme is secreted by various microorganisms, but bacterial PHB depolymerases are the most widely studied. The biodegradability rate depends on various factors. By controlling them, the biodegradability rate can change and be customized, and thus, the applications of the polymer can increase and become more diverse. In this work, the role of organomodified montmorillonite (OMMT) on PHB biodegradation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The rates for the best depolymerase/polyester pairs were up to 0.28 g/h/cm 2 . Depending on the provenance of the PHB depolymerase, either monomer and dimer of 3-hydroxybutyric acid or oligomers can be obtained. Doi et al also reported that the surface erosion of P3HB and P3HB- co -P4HB was faster while carrying surface erosion with PHB-depolymerase at 37 °C than by uncatalyzed hydrolytic bulk erosion at 55 °C …”
Section: End-of-use Optionsmentioning
confidence: 99%
“…The rates for the best depolymerase/polyester pairs were up to 0.28 g/h/cm 2 . Depending on the provenance of the PHB depolymerase, either monomer and dimer of 3-hydroxybutyric acid or oligomers can be obtained. Doi et al also reported that the surface erosion of P3HB and P3HB- co -P4HB was faster while carrying surface erosion with PHB-depolymerase at 37 °C than by uncatalyzed hydrolytic bulk erosion at 55 °C …”
Section: End-of-use Optionsmentioning
confidence: 99%
“…11 Mechanical properties have also been improved such as the storage module which has increased by 85%. 12 On the other hand, it has been determined that there is a minimal effect on the degree of crystallization and melting temperature when working with clays such as Na-montmorillonite and modified montmorillonite (Cloisite®15A and C93A). 13 The clays not only improve the mechanical, thermal and barrier properties of the polymers but also make it possible to encapsulate active ingredients, which give new features to the polymers such as antioxidant, antibacterial or antifungal activity.…”
Section: Introductionmentioning
confidence: 99%